La notion de recommandation numérique : essai de conceptualisation - Conte, Charlotte Le (Université de Reims Champagne-Ardenne, 2026)
Résultats de recherche, fils d’actualités, avis en ligne, communications d’influenceurs, publicités en ligne … Tout autant de pratiques incitatives permettant à l’internaute de se repérer au sein d’une offre pléthorique de contenus en ligne et pouvant a priori correspondre à l’expression de « recommandation numérique ». La notion de recommandation numérique n’a pourtant fait l’objet d’aucune conceptualisation alors même qu’il existe un régime juridique y afférent. Dès lors, la mise au jour de cette notion apparaît nécessaire afin d’identifier puis de qualifier ce qui déclenchera l’application de règles particulières.L’identification de la notion de recommandation numérique permet d’abord de la situer aux côtés de deux notions avec lesquelles elle entretient des liens de parenté parfois contradictoires : l’information et la publicité.L’étude propose dès lors deux séries de critères de qualification aptes à saisir la notion de recommandation numérique qui en impacte le périmètre. D’un point de vue matériel, la recommandation numérique possède une nature formelle : il s’agit d’un ordonnancement suggestif de contenus et non d’un contenu incitatif. Cette nature est corroborée par l’existence d’un régime juridique lui aussi formel car fondé sur la transparence, tandis que les contenus incitatifs sont soumis à des règles de fond. D’un point de vue fonctionnel, il s’agit d’une intermédiation informationnelle plus large qu'imaginée notamment parce qu'elle peut être de nature personnalisée ou non. Elle demeure néanmoins fondée sur un traitement algorithmique de données à caractère personnel ou non personnel et donc, soumise au droit des données. Search results, news feeds, online reviews, influencer communications, online advertising ... These are all incentive practices that enable internet users to find their way through a plethora of online content and could, in principle, be described as “digital recommendations”. However, the notion of digital recommendation has not been conceptualized, even though there is a legal framework governing it. It is therefore necessary to clarify this concept in order to identify and define what will trigger the application of specific rules.Identifying the notion of digital recommendation allows us to situate it alongside two concepts with which it has sometimes contradictory links: information and advertising.The study therefore proposes two sets of qualification criteria that capture the concept of digital recommendation and its scope. From a material point of view, digital recommendation is formal in nature: it is a suggestive ordering of content rather than incentive-based content. This nature is corroborated by the existence of a legal regime that is also formal, as it is based on transparency, whereas incentive-based content is subject to substantive rules. From a functional point of view, it is a broader form of information intermediation than imagined, particularly because it can be personalized or not. Nevertheless, it remains based on the algorithmic processing of personal or non-personal data and is therefore subject to data law.
Keywords: Algorithmes; Données; Droit de la consommation; Information; Intermédiation; Internet (droit); Publicité; Recommandation; Systèmes de recommandation (informatique)

Les pratiques déloyales dans les réseaux de distribution, mise à l'épreuve du droit de la concurrence - Ferré, Diane (Université Paris-Saclay, 2025)
A première vue, l'alliance des expressions "pratiques déloyales" et "réseaux de distribution" pourrait offusquer. Pourtant, le faible pouvoir de négociation du distributeur en réseau est à l'origine de pratiques déloyales occasionnées par le promoteur.Face à ce constat liminaire, la présente étude s'interroge : le droit de la concurrence, est-il suffisamment adapté pour se saisir de ce phénomène des pratiques déloyales dans les réseaux de distribution ? Ou au contraire, les règles générales ne seraient-elles pas devenues suffisamment obsolètes pour que l'on se décide à développer un régime sui generis ?Tout l'enjeu est alors de déterminer si, à l'instar des règles précédentes, le droit positif ne gagnerait pas à s'enrichir de mécanismes spécifiques pour lutter contre les pratiques déloyales au sein des réseaux de distribution.A cette dernière interrogation, nous avons répondu de façon nuancée. En premier lieu, nous évoquerons l'aménagement des règles substantielles du droit de la concurrence. De l'étude approfondie des règles du droit des pratiques anticoncurrentielles en passant par celles relatives aux pratiques restrictives de concurrence, le droit positif gagnerait à modifier ses règles pour s'adapter pleinement à la problématique des pratiques déloyales dans les réseaux de distribution.Cependant, parce que ces dernières règles resteraient ineffectives sans un cadre processuel adapté, notre étude nous a amené, en second lieu, à éprouver les règles processuelles. Si nous ne prônons pas une refonte intégrale des mécanismes, certains aménagements spécifiques s'imposent pour que ces règles soient adaptées à la problématique des pratiques déloyales dans les réseaux de distribution. At first glance, the combination of the terms ‘unfair practices' and ‘distribution networks' may seem offensive. However, the weak bargaining power of network distributors is at the root of unfair practices caused by the promoter.Given this preliminary observation, this study asks: is competition law sufficiently adapted to address the phenomenon of unfair practices in distribution networks? Or, on the contrary, have the general rules become sufficiently obsolete that we should decide to develop a sui generis regime?The challenge is therefore to determine whether, as with previous rules, positive law would benefit from being enriched with specific mechanisms to combat unfair practices within distribution networks.We have responded to this last question in a nuanced manner. Firstly, we will discuss the adjustment of the substantive rules of competition law. From an in-depth study of the rules of anti-competitive practices to those relating to restrictive practices, positive law would benefit from modifying its rules to fully adapt to the issue of unfair practices in distribution networks.However, because these rules would remain ineffective without an appropriate procedural framework, our study led us, secondly, to examine the procedural rules. While we do not advocate a complete overhaul of the mechanisms, certain specific adjustments are necessary to ensure that these rules are adapted to the issue of unfair practices in distribution networks.
Issue: 2025UPASH006
Keywords: Arbitres (droit); Circuits de distribution; Competition; Concurrence; Distribution networks; Pratiques déloyales; Procedure; Procédure; Recours collectifs (droit); Réseaux de distribution; Unfair practices

Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Issue: 2024ULILD015
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

L'après-franchise (?)... Le contrat de partenariat : nouveau modèle de contrat de distribution - Descazaux, Marcel-Philippe (Université de Montpellier, 2023)
L'après franchise (?)... le contrat de partenariat... nouveau modèle de contrat de distributionLes réseaux de franchise et le contrat qui les sous-tend sont aujourd'hui incontournables. Toutefois, le monde et le commerce sont en constante évolution. À tel point, que d'aucuns parlent d'une « crise » de la franchise. De nouveaux enjeux juridiques ont-ils vus le jour ? La maturité des réseaux actuels de franchise, le développement des concepts de commerce équitable, d'économie solidaire et le mode de fonctionnement des nouvelles générations tendent-ils vers un nouveau modèle contractuel plus horizontal ? A la marge des contrats de distribution en réseau « traditionnels », le contrat dit « de partenariat » occuperait aujourd'hui une place en progression constante, en prétendant répondre aux problématiques ci-dessus. Les observateurs relèvent, dans le même temps, que ce système de distribution en réseau semble peiner à s'affirmer et à être reconnu, notamment dans son cadre juridique. Le temps semble venu de vérifier si le contrat de partenariat n'est qu'une variante des autres modèles de contrats de distribution, notamment celui d'une franchise devenue éthique, ou bien s'il est un système spécifique et autonome de distribution. Constatant l'autonomie, cette thèse ambitionne de modéliser et de qualifier juridiquement le contrat de partenariat, en proposant des solutions novatrices aux freins avérés, afin de participer à son avènement.
Keywords: Chartes; Circuits de distribution; Collective interest; Contrat de partenariat; Distribution networks; Franchise; Franchising; Intérêt collectif; Know-How; Partenariat public-privé; Partnership agreement; Partnership-Knowledge; Réseaux de distribution; Savoir-Faire; Savoir-Partenarial

Merchandising e o princípio da identificação da publicidade - Filomeno, Jose Geraldo Brito (Universidade de São Paulo, 2023)
O fenômeno da globalização, decorrente do avanço tecnológico e consequente encurtamento das distâncias em face da massificação dos meios de transporte, promoveu o deslocamento da base econômica do sistema produtivo para o sistema de consumo, bem como aumentou a oferta de produtos e serviços no mercado. Com isso, instigou-se a batalha diária entre os fornecedores para conquistar a liderança da concorrência, ou mesmo manter-se no mercado, visível, segundo o jargão que quem não é visto não existe. Para tanto, fornecedores e agências de publicidade e propaganda recorrem aos meios de comunicação de massa, sendo mais presentes na televisão em razão da força desse veículo no atendimento do desiderato de investir no discurso subjetivo a fim de penetrar no imaginário do consumidor, por meio de técnicas de persuasão/sedução que o induzem a desejar o produto ou serviço objeto de publicidade e propaganda, no caso deste trabalho, por meio do merchandising. E hodiernamente esse fenômeno está igualmente nas redes sociais, onde se destacam os autodenominados influenciadores ou youtubers que, destacando-se por algum motivo (música, gastronomia, cosmetologia etc.), são logo contratados para seus poucos minutos de mensagens trazendo conselhos mas cuja eficácia depende de produtos determinados. Considerados esses fatores, este trabalho tem por objetivo analisar a prática do merchandising no Brasil com o propósito de distinguir entre o que é bom e, portanto, aceitável diante das normas legais, no Código de Defesa do Consumidor, e de cunho moral, insertadas no Código de Autorregulamentação Publicitária, e o que é ruim e condenável e, portanto, merecedor da fiscalização, pelo Estado e outros não-governamentais, para garantir segurança ao consumidor, figura considerada vulnerável nas relações de consumo diante das técnicas de persuasão adotadas pelas agências de publicidade e propaganda, bem como pelos fornecedores de produtos ou serviços. As questões discutidas no decorrer do trabalho interessam não apenas aos profissionais do Direito, como também, como é curial, àqueles vinculados à atividade publicitária, notadamente no que toca à ética e às técnicas que a devem presidir, bem como a tantos quantos se dediquem ao estudo dos fenômenos psicológicos, porquanto as mensagens publicitárias contêm uma considerável dose de apelo às percepções conscientes e subconscientes e, quiçá, das inconscientes, sendo certo que nesse terceiro aspecto residem as maiores polêmicas atinentes ao merchandising.
Keywords: Abuses; Abusos; Acceptance; Aceitação; Identification Principle; Limites; Limits; Merchandising; Princípio da Identificação; Publicidade Subliminar; Understated Advertising

La protection des renseignements personnels du consommateur dans un système bancaire ouvert : étude comparative entre le droit canadien et le droit québécois ainsi que le droit de l'Union européenne et le droit français - Rakotomandimby, Lauriane (Université Laval, 2023)
Dans un marché bancaire oligopolistique, marqué par un nombre limité d'institutions bancaires et financières offrant des services bancaires de plus en plus innovants et attractifs à une quantité innombrable de consommateurs, le système bancaire ouvert a engendré la multiplicité de ces services, grâce aux entreprises de technologie financière qui se présentent comme des concurrentes de taille face aux banques traditionnelles. Désormais, le consommateur peut procéder à des transactions électroniques, dont celles relatives au paiement ou au transfert électronique de fonds, sans devoir passer au comptoir de sa banque traditionnelle. Depuis la mise en place du Règlement général sur la protection des données et de la Directive révisée sur les services de paiement au niveau de l'Union européenne, les entreprises commerciales peuvent avoir accès aux renseignements personnels, dont les données financières des clients de banques, notamment pour initier un paiement, par le truchement des interfaces de programmation d'applications. Toutefois, le traitement des renseignements personnels des consommateurs par les entreprises commerciales augmente le risque de vol d'identité, étant donné la présence d'une quantité impressionnante de données sur le Web, sans un contrôle adéquat pour en assurer la confidentialité. Les conséquences d'une fuite de ces données sont pourtant non négligeables, aussi bien à l'égard de la banque, de la personne concernée que de l'État qui doit en assurer une protection optimale. Devant ce phénomène où le consommateur est vulnérable, l'État intervient pour le protéger et contrebalancer le déséquilibre dans sa relation contractuelle avec les prestataires de services financiers.
Keywords: Approche comparée; Confidentialité des données; Consommateur; Droit comparé

L'efficacité du recouvrement par l'Etat des recettes fiscales de la taxation sur la consommation : Etude du cas de la TVA au Togo - Tchitare, Mawèdéou (Université de Montpellier, 2022)
Le but de notre étude est de parvenir à un recensement puis à une typologie des difficultés en matière fiscale au Togo, précisément en termes de TVA, notamment le vécu quotidien entre l'Administration et les contribuables. Ainsi arriverons-nous, au travers des données tirées de nos différentes sources, à apporter des solutions aux difficultés ainsi répertoriées en incitant vivement l'Etat à la revalorisation et à la récupération des recettes fiscales inhérentes à la ressource TVA. L'intérêt porté à la TVA découle de l'importance de cet impôt au regard du volume des recettes fiscales étatiques. The aim of our study is to get to a census and to a typology of difficulties as far as fiscal system is concerned in Togo precisely concerning VAT, especially the experienced of relations between the Civil Service and the taxpayers. Thus, we will get trough some drawn data of our various sources, to bring solutions to problems thereby catalogued by urging vividly the state to the redress, to the revaluation, and to the recovery of fiscal incomes inherent to the VAT resource. The interest in VAT arises from the importance of this tax in relation to state's tax revenues.
Issue: 2022UMOND030
Keywords: Consumption taxing; Efficacité; Efficiency; Fiscal receipts; Recettes fiscales; Recouvrement; Recouvrement de l'impôt; Recovery; TVA; Taxation sur la consommation; Taxe sur la valeur ajoutée; Togo; VAT

El huésped-consumidor como sujeto internacional de protección frente a las plataformas en línea de alojamientos turísticos - Canales Gutíerrez, Silvana (Universitat Rovira i Virgili, 2022)
Els hostes com a consumidors en el marc del contracte d'intermediació digital amb element internacional subscrit amb una plataforma en línia per a allotjaments turístics, poden ser subjectes d'especial protecció tant per les normes de Dret internacional privat com per les normes substancials de protecció al consumidor de cada Estat. Aquesta recerca exposa el panorama actual i comparat de protecció dels consumidors en matèria de competència judicial internacional, llei aplicable i normes imperatives a la Unió Europea i a Colòmbia, Mèxic, l'Argentina i el Brasil. D'una banda, l'anàlisi es centra en les plataformes en línia per a allotjaments turístics, el seu passat col·laboratiu, la seva estructura societària, la redacció dels seus termes i condicions i les seves obligacions actuals enfront del canvi que suposarà el Digital Services Act. D'altra banda, s'aplica la normativa de competència judicial internacional i llei aplicable (RBIbis i RRI) a la Unió Europea i en els sistemes de Dret internacional Privat dels estats llatinoamericans seleccionats, al contracte d'intermediació entre la plataforma i l'hoste-consumidor quan es presenta una controvèrsia i aquest últim, d'acord amb criteris com el seu domicili o residència habitual, es troba protegit en diferents nivells que només poden considerar-se més o menys favorables en l'anàlisi del cas concret.
Keywords: Allotjament turístic; Alojamiento turístico; Ciències Socials i jurídiques; Consumer; Consumidor; Online platform; Plataforma en linea; Plataforma en línia; Tourist accommodation

Las causas de extinción de los contratos de distribución comercial - Lascorz Collada, María-Cruz (Universitat de Barcelona, 2022)
[spa] En el presente trabajo de investigación se examinan las causas de terminación de las relaciones distributivas. Los contratos de distribución resultan una pieza fundamental para el funcionamiento del mercado y una herramienta clave de la economía globalizada al servicio de las empresas en los negocios internacionales. A pesar de las propuestas nacionales e internacionales de regulación de estos contratos, la ausencia de una normativa aplicable en el ámbito de la distribución plantea notables problemas empresariales que carecen de soluciones jurídicas. Se analizan sistemáticamente los problemas que suscita la extinción de los contratos de distribución, tanto a la vista de los casos planteados como de las soluciones que se ofrecen en la práctica. En concreto, se estudian los supuestos motivados por el desistimiento unilateral ad nutum, la resolución por incumplimiento del contrato, la alteración sobrevenida de circunstancias o la incidencia del intuitu en la conservación de los contratos; tanto en los ordenamientos jurídicos continentales como en los sistemas de la órbita del Common Law. Confrontadas las opciones ofrecidas por el Derecho comparado, se extraen algunas soluciones de sistemas proteccionistas propias del Derecho anglosajón, como el Derecho estadounidense o australiano, o de ordenamientos semiproteccionistas con la parte débil del contrato como el Derecho francés. Todo ello con la finalidad de valorar la oportunidad de adoptar una regulación que atienda de manera específica a las necesidades del sector de la distribución, sin prescindir de una adecuada técnica jurídica con las conexiones oportunas con el sistema jurídico en su conjunto. Además de exponer las modulaciones que experimentan en el sector distributivo algunos de los principios básicos del Derecho de contratos, la investigación concluye abordando un conjunto de propuestas normativas y contractuales concretas que podrían contribuir a la reducción de la conflictividad de las relaciones distributivas. Y, por ende, a la disminución de la litigiosidad entre las mismas, dadas las características particulares de estos contratos duraderos, relacionales y colaborativos.
Keywords: Ciències Jurídiques; Commercial law; Contractes de distribució comercial; Contrat de distribution; Contratos de distribución comercial; Derecho mercantil; Distribution Agreement; Distribution commerciale; Distribution contracts; Dret mercantil; Econòmiques i Socials; Extinció de les obligacions; Extinción de obligaciones; Extinguishment of debts

Le renouvellement de la sanction en droit économique contractuel - Lefeuvre, Noémie (Université de Rennes 1, 2021)
Le droit économique contractuel est une discipline fondamentalement contemporaine, qui évolue avec son temps et les avancées sociétales. Droit très protecteur, il a pour but de protéger non seulement le marché, mais également les différents contractants, en priorité la partie faible au contrat. Son champ d’intervention, le droit de la consommation et le droit des pratiques restrictives de concurrence, a donc subi une légifération exponentielle ces quarante dernières années. Mêlant volonté de régulation et d’efficacité des procédures tout en ménageant les entreprises françaises, le législateur a construit un régime autour de trois grands types de sanctions : les sanctions civiles, pénales et administratives. Sans jamais faire disparaître les unes au profit des autres, les sanctions en droit économique contractuel forment aujourd’hui un panel très diversifié qui doivent coexister les unes avec les autres. Aux côtés des sanctions civiles, qui se renouvellent doucement, les sanctions non civiles, que sont les sanctions pénales et administratives, prennent de plus en plus d’ampleur au sein du droit économique contractuel. Afin de les distinguer les unes des autres, il est indispensable de reprendre les fondements de la notion de sanction et d’étendre cette recherche à chacune des sanctions. Les sanctions non civiles, répressives par nature, répondent certes à un objectif de protection de l’ordre public économique renforcé, mais ont également été mises en place en vue de bénéficier des facilités procédurales qu’elles apportent. Il est alors impératif de remodeler la sanction en droit économique contractuel et la procédure qui l’accompagne.
Keywords: Actions collectives; Actions individuelles; Class actions; Commercial law; Consommateur (protection); Consumer law; Contract law; Contrat; Damages; Dgccrf; Droit de la consommation; Droit des pratiques restrictives de concurrence; Droit économique; Economic public policy; France; Ordre public économique; Procedure; Procédure; Procédure pénale; Sanction; Sanctions administratives; Sanctions civiles; Sanctions non civiles; Sanctions pénales; Sanctions économiques; Sentences

La protection du consommateur dans la vente en ligne en Côte d'Ivoire : Etude à la lumière du Droit européen - Adde, Franck Olivier (Université de Luxembourg, 2021)
Like most African countries, Côte d'Ivoire is experiencing a rapid growth in e-commerce. This boom brings challenges of all kinds. Amidst others, it is taking in a legal context where consumer protection has not yet found its place, as evidenced by the texts of laws governing distance selling in Côte d'Ivoire. The thesis aims to propose an improvement of consumer protection in distance selling in Côte d'Ivoire through a review of laws in the light of European law. Though it refers to the European legal model, the thesis stresses that the literal mimicry of European law is one of the reasons for the ineffectiveness of African laws. The premise of the thesis about distance selling is that we cannot protect the consumer in the ivory coast in the same way that European law protects the European consumer. Beyond a simple legal comparison, the thesis stirs an in-depth reflection on the circulation of legal models. It examines the relationship between African law and European law from a historical and contextual point of view in order to determine how European law can serve as a model for Ivorian law so as to offer sufficient protection to consumers without threatening the growth of distance sales. Comme la plupart des pays africains, la Côte d’Ivoire connaît une croissance rapide du commerce électronique. Ce boom pose des défis de toutes sortes. Parmi d’autres, elle s’inscrit dans un contexte juridique où la protection des consommateurs n’a pas encore trouvé sa place, comme en témoignent les textes de lois régissant la vente à distance en Côte d’Ivoire. La thèse vise à proposer une amélioration de la protection des consommateurs dans la vente à distance en Côte d’Ivoire à travers une révision des lois à la lumière du droit européen. Bien qu’elle fasse référence au modèle juridique européen, la thèse souligne que le mimétisme littéral du droit européen est l’une des raisons de l’inefficacité des lois africaines. Le postulat de la thèse sur le sujet de la vente à distance est celui d’affirmer que l’on ne peut pas protéger le consommateur en côte d’ivoire de la même manière que le Droit européen protège le consommateur européen. Au-delà d’une simple comparaison juridique, la thèse suscite une réflexion approfondie sur la circulation des modèles juridiques. Elle examine la relation entre le droit africain et le droit européen d’un point de vue historique et contextuel afin de déterminer comment le droit européen peut servir de modèle pour le droit ivoirien de sorte à proposer une protection suffisante aux consommateurs sans menacer la croissance des ventes à distance.
Keywords: Circulation des modèles juridiques; Commerce électronique; Consommateur (protection); Droit africain; Droit européen; Vente à distance

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Accepted: 2021-07-07T10:12:30Z
Keywords: Data Protection; Personal data; Privacy

La protection des emprunteurs de microcrédit : cadre juridique, pratiques institutionnelles et perceptions des acteurs au Bénin - Fonton, Appoline (Université Laval, 2021)
L'objectif de cette thèse est de réaliser dans le contexte béninois un état des lieux de l'effectivité de la protection des emprunteurs de microcrédit. Pour ce faire, sept principes de protection des emprunteurs ont été identifiés. Notre approche est inscrite dans une perspective semi-inductive de sociologie du droit permettant de combiner l'analyse de contenu des textes de loi à l'analyse d'observations directes et de données empiriques collectées auprès de 18 emprunteurs et de huit chefs d'agence à propos des sept principes de protection des emprunteurs préalablement identifiés. Nos résultats montrent qu'au plan juridique les sept principes de protection des emprunteurs bénéficient d'un encadrement très variable, allant d'un fort encadrement législatif pour le principe de confidentialité à un faible encadrement pour les principes de gestion des plaintes, de développement et distribution appropriés des microcrédits, puis de traitement respectueux et responsable. L'analyse des perceptions des divers acteurs permet de constater que si un fort encadrement législatif ne conduit pas toujours vers une bonne protection des emprunteurs contre les risques, un faible encadrement législatif n'induit pas non plus obligatoirement un faible niveau de protection. Plusieurs écarts entre normes juridiques et pratiques institutionnelles ont été identifiés comme en ce qui concerne la confidentialité des informations personnelles de la clientèle. Il a aussi été possible de repérer quelques innovations pratiques dans le secteur comme la mise en place d'un réseau local d'information sur l'endettement des demandeurs de microcrédit permettant de contourner, non pas sans difficultés l'inexistence d'un Bureau d'information et de crédit pour protéger les emprunteurs contre le surendettement. Au regard des résultats, il importe que des actions concrètes d'éducation, de supervision et d'amélioration de la réglementation soient mises en œuvre pour améliorer la protection des emprunteurs de microcrédit. Au-delà des nécessaires réajustements du cadre réglementaire à travers par exemple l'instauration d'un dispositif de gestion des plaintes, d'aide à l'analyse de la capacité de remboursement des clients, de supervision de la confidentialité des données, l'accent doit être véritablement mis sur le renforcement de la surveillance et la sensibilisation des divers acteurs. Il serait aussi opportun de réfléchir à la mise en place de programmes de microcrédit intégré incluant le microcrédit, l'alphabétisation, la micro-assurance ainsi que la formation à la littératie financière. The objective of this thesis is to carry out the situation of the effectiveness of the protection of microcredit borrowers in the Beninese context. To do this, seven principles of borrower protection have been identified. Considering these principles, our approach is based on a perspective of semi-inductive sociology of law that combines content analysis of legal texts with analysis of direct observations and empirical data collected from 18 borrowers and 8 agency heads. Our results show that, from a legal point of view, the seven principles of borrower protection benefit from a very variable framework, ranging from a solid legislative framework for the principle of confidentiality to a weak framework for the principles of complaint management, the development and appropriate distribution of microcredits, and the respectful and responsible treatment. The analysis of the perceptions of the various actors shows that while a solid legislative framework does not always lead to adequate protection of borrowers against risks, a weak legislative framework does not necessarily induce a low level of protection either. Several gaps between legal standards and institutional practices have been identified, for example, the confidentiality of personal information of clients. It was also possible to identify some practical innovations in sectors like the establishment of a local information network on the debt of microcredit applicants to bypass, not without difficulty, the lack of an Information and Credit Office to protect borrowers against over-indebtedness. Considering the results, it is important that concrete actions of education, supervision and better regulation are implemented to improve the protection of microcredit borrowers. Beyond the necessary readjustments to the regulatory framework through, for example, the introduction of a complaints management system, assistance in analyzing clients' repayment capacity and supervision of data confidentiality, real emphasis must be placed on strengthening monitoring and raising awareness among the various stakeholders. It would also be appropriate to consider the implementation of integrated microcredit programmes including microcredit, microinsurance and financial literacy training.
Keywords: Culture financière; Droit à la vie privée; Débiteur et créancier; Microcrédit (droit); Pauvres (droit); Sécurité financière

La distribution automobile : étude comparée - Hocini, Mustapha (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
Le législateur algérien a fait le choix au moment crucial de réguler le secteur de la distribution automobile par une règlementation spéciale, considérée comme un instrument de lutte contre l’anarchie et favorisant la sécurité juridique dans ce secteur. L'objectif poursuivi était le suivant : combattre les dysfonctionnements et les anomalies du marché de la commercialisation des véhicules automobiles neufs et garantir une protection au consommateur qui était totalement livré à lui-même. Les nouvelles conditions prévues par le législateur algérien portent sur les procédures administratives, les conditions d’exercice de l’activité de concessionnaires de véhicules neufs, le service après-vente ainsi que la garantie et les délais de livraison auxquels est soumis le concessionnaire automobile. L'objectif principal de cette étude est d’évaluer cette nouvelle règlementation à travers une approche comparative avec le droit européen et le droit français applicables à la distribution automobile. Il s’agit pour cela d’insister sur les différences, ou encore essayer d’identifier des principes communs à ces systèmes juridiques. Ainsi il serait possible de détecter les lacunes en droit algérien et d’anticiper sur les problèmes que peut causer la nature complexe de la distribution automobile afin de bénéficier des expériences déjà acquises en droit européen et français, notamment en matière de pratiques anticoncurrentielles et d’équilibre contractuel. Dans un contexte de mondialisation et d'intégration régionale, la présente étude vise aussi à contribuer au développement de la relation entre l’Algérie et les pays de l’Union Européenne et particulièrement la France, en apportant une meilleure compréhension du système juridique algérien, à travers l'analyse comparée du contrat de distribution automobile, lequel exige une étude plus approfondie grâce à sa complexité, plus particulièrement en matière de droit des obligations, de la concurrence, et de la propriété intellectuelle. إختار المشرع الجزائري في وقت حاسم تنظيم نشاط توزيع السيارات من خلال نص قانوني خاص ، يعتبر كأداة لمكافحة الفوضى وتعزيز الأمن القانوني في هذا القطاع. كان الهدف من ذلك هو مكافحة الاختلالات والعيوب في سوق بيع السيارات الجديدة وتوفير حماية للمستهلك الذي كان مهملا بالكامل. تتعلق الشروط الجديدة التي حددها المشرع الجزائري بالإجراءات الإدارية، شروط ممارسة نشاط وكلاء المركبات الجديدة، وخدمة ما بعد البيع ، بالإضافة إلى الضمان ومواعيد التسليم التي يخضع لها موزع السيارات. إن الهدف الرئيسي من هذه الدراسة هو تقييم هذا النص القانوني الجديد من خلال منهجية المقارنة مع القانون الأوروبي والقانون الفرنسي المطبق على توزيع السيارات. لأجل هذا يتعلق الأمر بالتأكيد على الاختلافات، أو محاولة تحديد المبادئ المشتركة لهذه النظم القانونية. بالتالي ، سيكون من الممكن اكتشاف الثغرات في القانون الجزائري وتوقع المشاكل التي قد تنجم عن الطبيعة المعقدة لتوزيع السيارات من أجل الاستفادة من الخبرات المكتسبة بالفعل في القانون الأوروبي والفرنسي ، لا سيما فيما يتعلق بالممارسات المنافية للمنافسة و التوازن التعاقدي. في سياق العولمة والاندماج الإقليمي ، تهدف هذه الدراسة أيضًا إلى المساهمة في تطوير العلاقة بين الجزائر ودول الاتحاد الأوروبي وخاصة فرنسا ، من خلال تقديم فهم أفضل للنظام القانوني الجزائري ، عن طريق التحليل المقارن لعقد توزيع السيارات ، والذي يتطلب دراسة أكثر تعمقا بسبب تعقيده، وخاصة فيما يتعلق بقانون الالتزامات والمنافسة والملكية الفكرية. The Algerian legislator made the choice at the crucial moment to regulate the automobile distribution sector by a special regulation, considered as an instrument of fight against lawlessness and promoting legal security in this sector. The objective was to combat malfunctions and anomalies in the market for the sale of new motor vehicles and to provide protection to the consumer who was completely left alone. The new conditions stipulated by the Algerian legislator concern the administrative procedures, the conditions of exercise of the activity of dealers of new vehicles, the after-sales service as well as the guarantee and the delivery times to which the car dealer is subjected. The main objective of this study is to evaluate this new regulation through a comparative approach with European law and French law applicable to car distribution. This involves emphasizing the differences, or trying to identify principles common to these legal systems. Thus it would be possible to detect deficiencies in Algerian law and to anticipate the problems that may be caused by the complex nature of automobile distribution in order to benefit from the experiences already acquired in European and French law, particularly with regard to anti-competitive practices and contractual balance. In a context of globalization and regional integration, this study also aims to contribute to the development of the relationship between Algeria and the countries of the European Union and particularly France, by bringing a better understanding of the Algerian legal system, through the comparative analysis of the automobile distribution contract, which requires a more in-depth study because of its complexity, particularly in terms of the law of obligations, competition, and intellectual property.
Keywords: Consommateur (protection); Distribution automobile (règlementation); Droit algérien; Legal security; Sécurité juridique; Véhicule automobile

Savoir-faire et franchise - Nadal, Mathieu (Université Côte d'Azur, 2020)
A l’instar de l’obligation d’assistance ou de la mise à disposition de signes distinctifs, le savoir-faire constitue un élément essentiel du contrat de franchise. En dépit de son importance, le législateur a fait le choix de ne pas le définir. Il est donc revenu à la jurisprudence ainsi qu’à la doctrine de dégager les éléments constitutifs du savoir-faire. Par ailleurs, l’importance du savoir-faire au sein du contrat de franchise se matérialise à travers l’étendue des obligations que chacune des parties devra supporter tout au long de la relation contractuelle. En raison de sa valeur patrimoniale importante, le franchiseur devra prendre toutes les mesures qui s’imposent afin de préserver son savoir-faire. Le franchiseur pourra avoir recours à différentes actions, civiles ou pénales, afin d’obtenir d’une part, la réparation de son préjudice et d’autre part, la condamnation de l’auteur de l’atteinte au savoir-faire.
Keywords: Circuits de distribution; Concessions (commerce de détail); Responsabilité contractuelle; Savoir-faire industriel

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

الإشهار الخادع: دراسة مقارنة - موسى, نسيمة (Ibn Khaldun University of Tiaret, 2020)
يدور المحور الرئيس للموضوع حول جريمة الإشهار الخادع دراسة مقارنة بين كل من التشريع الجزائري والفرنسي والمصري، حيث يمكن إعطاء تعريف لهذه الجريمة على أنها إعلان يتضمن عرضا، او بيانا أو إدعاء كاذب ومضلل، أو أي أمر يؤدي بطريقة مباشرة أو غير مباشرة إلى خلق إنطباع حقيق أو مضلل، أو تقديم معلومات غير دقيقة وبالتالي تؤدي إلى إنطباعات مخادعة تغري المستهلكين بالشراء بناءا على تلك المعلومات، لذلك عملت مختلف التشريعات على وضع ضوابط العمل في المجال الإشهاري وهو ماتصدى له المشرع الجزائري من خلال جملة من النصوص القانونية التي أوردها في كل من القانون رقم 04/02 المتعلق بالقواعد المطبقة على الممارسات الأنشطة التجارية لاسيما المادة 28 منه، بالإضافة إلى قانون العقوبات مع العلم أنه في الجزائر لا يوجد قانون خاص بالإشهار على عكس التشريعين الفرنسي والمصري حيث يوجد لديهم قانون خاص ينظم عملية الإشهار، ولمعرفة الحماية المكفولة للمستهلك منها سوفى نتولى دراستها من الجانب المدني أي الحماية المدنية ثم الشق الجزائي أي الحماية الجنائية.
Keywords: Biens; Criminalité; Marketing; Protection juridique; Protection pénale; Publicité; Services; Tromperie